THE RIGHT TO THE HIGHEST ATTAINABLE STANDARD OF MENTAL HEALTH IN SELECTED AFRICAN COUNTRIES: A COMMENTARY ON HOW SELECTED MENTAL HEALTH LAWS FARE AGAINST ARTICLE 25 OF THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES (African Disability Rights Yearbook, 2021)
Persons with disabilities have an equal right to access health services, including general health services and disability-related health services. In accessing health care, persons with disabilities encounter many barriers. These include stereotypes about disability on the part of health care providers; a lack of appropriately-trained health care staff; imbalanced power relationships between persons with health needs and medical professionals; inaccessible health care facilities; inaccessible health-related information; and a lack of individualised accommodations.1 These barriers are heightened in the circumstances of persons with psychosocial disabilities who face additional challenges, including legally-sanctioned involuntary commitment; forced treatment; and the use of restraints and solitary confinement in mental health care institutions.In addition, certain categories of persons with psychosocial disabilities require particular attention in health care settings. In this regard, the Special Rapporteur on Torture and Other Cruel, Inhuman or Degrading Treatment in his 2013 report notes that ‘women living with disabilities, with psychiatric labels in particular, are at risk of multiple forms of discrimination and abuse inhealth-care settings’.2
Keywords: Persons with disabilities; right to access health services; psychosocial disabilities; the Special Rapporteur on Torture and Other Cruel, Inhuman or Degrading Treatment; 2013